Heterotopic Ossification in the Abdominal Wall after Exploratory Laparotomy - Hohyun Kim (Journal of Trauma and Injury)
Heterotopic bone formation in abdominal incisions is a recognized but uncommon sequela of abdominal surgery. On the other hand, the formation of ectopic bone is a well-recognized complication following arthroplasty of the hip. Heterotopic ossification of midline abdominal incision scars is a subtype of myositis ossificans traumatica. Ectopic bone formation of midline abdominal incisions may cause regional pain or discomfort in the patient after surgery. If symptomatic, treatment is complete excision with primary closure. Radiologically, it is important to distinguish this benign entity from postoperative complications. We report a 69-year-old male who underwent exploratory laparotomy for traumatic small bowel perforation. A segment of abnormal hard tissue was found in the abdominal wall. Heterotopic ossification may occur at various sites and is a recognized but infrequent sequela of exploratory laparotomy. This case high-lights clinical and etiological features of this finding.